Effect of counter anions on ferroelectric properties of diisopropylammonium‐cation based molecular crystals. Issue 6 (22nd March 2017) - Jiang, Chunli; Tong, Wen‐Yi; Lin, Hechun; Luo, Chunhua; Peng, Hui; Duan, Chun‐Gang
Abstract : Diisopropylammonium cation based single crystals with different counter anions (F −, Cl −, Br −, I −, N O 3 −, and C l O 4 − ) were prepared. Their crystal structures and ferroelectric properties were investigated by single‐crystal X‐ray diffraction spectroscopy, differential scanning calorimetry, and dielectric measurements. The experimental results illustrate that the ferroelectric properties of diisopropylammonium‐based single crystals are closely related to the electronegativity and structure of the counter anions. For monoatomic anions, higher electronegativity results in higher polarization and phase‐transition temperature of the corresponding molecular–ionic ferroelectrics. The results of density‐functional theory (DFT) calculations also support the experimental results.